Response of Standard Rooting System to Leachates and Alcoholic Extracts from Difficult to Root Arboreal Species - Sharma, V. (Indian Forester, 2012)
Leachates and alcoholic extracts (10%) from potential hardwood cutting material were prepared from Pinus wallichiana,Cedrus deodara, Abies pindrow, Thuja orientalis, Aesculus indica, Rhododendron arboreum, Magnolia grandifolia and Quercus incana, that grow around Shimla -the mid Himalayas. Rooting response of standard hypocotyl cutting system (Cucumis sativus L. 8 day old cuttings that form, on average, 14 roots by ninth day of suspension in water at 25 Â± 1Â°C continuous light) to 10, 100 and 1000 times dilutions of original extract were recorded. Concentrated leachates from wood of all species were toxic while rooting was slightly prormoted at 1000 and 100 times dilutions of original extract. Alcoholic extracts were toxic even at 100 times dilutions while 1000 times dilutions slightly promoted rooting of standard hypocotyl rooting systems. Residue of alcoholic extract applied after dissolution in water promoted rooting at 1000,100 and 10 times dilutions as well.